Hotel Employee Acceptance Assessment System With Android-Based Moora Method - Karpen Karpen; Widi Paramita; Triyani Arita Fitri; Koko Harianto (STMIK Amik Riau, 2020)
Hotel is a company engaged in the field of services, which requires employees who have competencies in accordance with their fields. At present the existing employees are deemed to lack competency in accordance with their field of work. In order for employees to have competence according to their field of work, the hotel must carry out an acceptance assessment that requires certain criteria, such as education, foreign language acquisition, discipline, experience and others. One of the appropriate decision making methods for evaluating acceptance is the MOORA (Multi Objective Optimization on the basis of Ratio Analysis) method which is a multi-objective system that optimizes two or more conflicting criteria. The MOORA method has a degree of flexibility and ease of understanding in separating the subjective parts of an evaluation process into criteria, by determining the weights and attributes as decision making, the form of decision matrices and ranking. The criteria used in this study are height, experience, discipline, interviews, written tests, foreign languages, friendly, computer, software and medical checkups. To facilitate the assessment of acceptance, this system is applied based on Android, so that in addition to the hotel, prospective employees can also find out the results of the assessment. Based on the implementation of the system application, the use of the MOORA method for the hotel employee acceptance evaluation system can produce the right decision system, in accordance with the predetermined ranking, criteria and weight of the assessment